Modification of properties of the glass-Si₃N₄-Si-SiO₂ structure at laser treatment - Konakova, R.V.; Kladko, V.P.; Lytvyn, O.S.; Okhrimenko, O.B.; Konoplev, B.G.; Svetlichnyi, A.M.; Lissotschenko, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
We studied the effect of laser treatment on the glass-Si₃N₄-Si-SiO₂ structures. It is shown that laser treatment causes appearance of an additional band in their transmission spectra as well as smearing of grain structure at their surface.